2014
DOI: 10.4025/actascianimsci.v36i1.18993
|View full text |Cite
|
Sign up to set email alerts
|

<b>Nutritional value of Xaraes and Piata palisadegrass silages prepared with additives or wilting</b>

Abstract: ABSTRACT. The nutritional value of Xaraes and Piata palisadegrass silages wilted or with additives was evaluated in a completely randomized design (2x4 factorial arrangement), being two cultivars of Brachiaria brizantha (Xaraes and Piata palisadegrass) and four ensiling methods as treatments: T 1 -control, in natura forage (INF); T 2 -INF wilted for 4 hours under the sun; T 3 -INF + bacterial additive (BactoSilo® Lallemand) 2 g ton -1of in natura forage; T 4 -INF + 15% of pearl millet meal. For ensiling, the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…Fresh mulberry silage did not differ significantly from the other silages in terms of EC values (1079.08 mS cm -1 ). Higher values of EC were observed in legume silage due to higher concentration of soluble components and ions compared to grass silage (BAMBIERIS JUNIOR et al, 2010;LIMA-OROZCO et al, 2013), which provides an explanation for the highest EC values in pre-wilted mulberry and fresh mulberry silages. In general, wilted silage resulted in higher cell lysis than non-wilted silage, resulting in higher EC (LOURES et al, 2005).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Fresh mulberry silage did not differ significantly from the other silages in terms of EC values (1079.08 mS cm -1 ). Higher values of EC were observed in legume silage due to higher concentration of soluble components and ions compared to grass silage (BAMBIERIS JUNIOR et al, 2010;LIMA-OROZCO et al, 2013), which provides an explanation for the highest EC values in pre-wilted mulberry and fresh mulberry silages. In general, wilted silage resulted in higher cell lysis than non-wilted silage, resulting in higher EC (LOURES et al, 2005).…”
Section: Resultsmentioning
confidence: 84%
“…The total loss in the ensiling process can be up to 20% of the ensiled mass (McDONALD et al, 1991) and, of that total, about 6.1% to 24.6% loss occurs during the fermentation (ZOPOLLATTO et al, 2009). In order to improve the fermentation pattern of silage, techniques such as wilting and the use of additives have been used to increase the DM content of the material before ensiling and to promote a more pronounced drop in pH, respectively (AZEVEDO et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For the treatment with cornmeal, the NDF values were reduced, since this additive is poor in fiber. Reduction in the fiber values were found by Azevedo et al (2014), in silage of Piatã grass, which showed 691.7 g kg -1 and 661 g kg -1 of NDF in the treatments with enzyme-microbial inoculant and with inclusion of millet meal, respectively, as compared with the control treatment (727.5 g kg -1 ).…”
Section: Chemical Compositionmentioning
confidence: 89%
“…The use of additives that contribute to the increase in dry matter content in grass silage is commonly used because of the low DM content in the development phase with better nutritional value (Azevedo et al, 2014;Epifanio et al, 2014;Silva et al, 2011). Therefore, the use of cornmeal is always the best option as an additive as well as other available meal.…”
Section: Chemical Compositionmentioning
confidence: 99%
See 1 more Smart Citation